When is agrivoltaics profitable compared to agriculture and photovoltaics? A joint-product economic feasibility analysis - Buzzelli, Maria, author; Mooney, Daniel, advisor; Hoag, Dana, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2024)
Solar is the fastest-growing renewable energy sector in the United States, however, land suitable for solar installations competes with productive agricultural land. Agrivoltaics (AV) offers a potentially promising solution by creating a dual use for land and improving crop yields. This paper examines the trade-offs between agricultural and solar production on a finite amount of land, using tomato cultivation as a case study. The study reveals a significant trade-off between energy production and crop yield. Scenarios maximizing energy production, particularly with bi-facial 5% transparent panels, generate the highest net revenues, highlighting the profitability of energy over agriculture. The rate of product transformation (RPT) indicates an inverse relationship between energy and crop production, averaging a 2% decrease in tons of crops per additional MWh of energy produced. Converting all available land to traditional photovoltaic (PV) solar panels is the most financially viable option for farmers, generating 12.4% more annual revenue as compared to only producing crops. The increase in crop yields from AV does not outweigh the additional costs associated with AV installation and maintenance. This paper identifies the subsidy levels required for AV to break even with crop production and with the traditional PV scenario. The results and discussion contribute to the economic literature on AV by highlighting key aspects of AV field configurations and related policy incentives to keep agricultural land productive while also growing the renewable energy sector.
Keywords: agriculture; economics; renewable energy; agrivoltaics; adoption; energy